PENGARUH MACAM PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL TIGA KULTIVAR KACANG HIJAU (Vigna radiata L. Wilczek) DI LAHAN PASIR PANTAI BUGEL, KULON PROGO - , TAUFIK AFIF ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Some coastel region at Bugel are as sand-dunes. Characteristics of the dunes are sand-textured soils, single grained structure, water holding capacity and the status of low fertility, high evaporation, and the strong sea wind. The addition of manure is believed to improve the nature of physics, chemistry and biology of the soil, therefore, a study used carried out to determine the effect of manure of cattle, goats, and chickens on growth and yield of three cultivars of mung bean (Vigna radiata L. Wilczek). The study was conducted at coastel Bugel, Yogyakarta in September-December 2013. The field experiment was designed as Complete Randomized Block Design (RCBD) with two factors. The first factor is the type of manure and the second factor as kind varieties (Vima-1, Murai, Kenari). The observed data at analyzed using analysis of variance (ANOVA) with the level of credibility at 5 %. If the results of the analysis of variance are significantly different formatting as between than followed by Duncan's Multiple Range Test (DMRT) at 5% level of confidence. To determine the relationship between parameters used in this study followed the correlation analysis. The results showed that the addition of goat manure could increase the vegetative growth of green bean plants. Chicken manure treatment resulted in seed weight per hectare higher at 1,84 tons per hectare compared to goat manure, cow manure and control. Murai cultivars have better vegetative growth than of most cultivars Vima-1 and Kenari. Kenari green bean cultivars capable of producing weight seeds per acre with the highest weight at 1,83 tons per hectare compared to cultivars Vima-1 and Murai.